Endoultrasound versus Conventional Image Guided (CT/US) Fine Needle Aspiration in Diagnosis of Pancreatic Malignancy (Journal of Surgical Sciences, 2021)
Background:The emergence of endoultrasound (EUS) has shown this modality to be an excellent method of detecting and staging lesions in the pancreas with a low rate of complications. Controversy has arisen about whether the approach with the conventional image (CT/US) guided FNA or endoultrasound (EUS) guided FNA is the preferred method to obtain cells from suspicious mass.Objectives:To assess the diagnostic efficacy of endoultrasound guided fine needle aspiration (EUS FNA) versus conventional imageguided fine needle aspiration (CT/US FNA) in pancreatic malignancy.Methodology:Twentyeight cases of clinically suspected patients of pancreatic malignancy were included in the study. Each enrolled patient underwent to either a conventional image guided fine needle aspiration or endoultrasound guided fine needle aspiration of the pancreatic mass for diagnosis of pancreatic malignancy. Data were analyzed with the help of SPSS version 23. Statistical analysis was done by student t-test and Chi square (÷2) test. Statistical significance was set at p